2018
DOI: 10.1002/cbin.11020
|View full text |Cite
|
Sign up to set email alerts
|

PKG II inhibits PDGF‐BB triggered biological activities by phosphorylating PDGFRβ in gastric cancer cells

Abstract: Previous studies revealed that type II cGMP-dependent protein kinase G (PKG II) could inhibit the activation of epidermal growth factor receptor (EGFR) which is a widely investigated RTK. PDGFR belongs to family of receptor tyrosine kinases (RTKs) too. However, the effect of PKG II on PDGFR activation is not clear yet. This study investigated potential regulatory effect of PKG II on activation of PDGFRβ and the downstream signaling transductions in gastric cancer. The results from CCK8 assay and Transwell assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Previous studies from our lab have found that PKG II blocked the activation of PDGFRβ by PDGF-BB, thereby inhibiting signal transduction initiated by PDGFRβ and related cell proliferation, migration, and other activities (Y. Wang et al, 2018). In addition, our recent data confirmed that PKG II could be secreted out of the cell and existed in the supernatant of cultured cells and human and mouse serum.…”
Section: Cell Ell B Biology Iology I International Nternationalsupporting
confidence: 78%
See 3 more Smart Citations
“…Previous studies from our lab have found that PKG II blocked the activation of PDGFRβ by PDGF-BB, thereby inhibiting signal transduction initiated by PDGFRβ and related cell proliferation, migration, and other activities (Y. Wang et al, 2018). In addition, our recent data confirmed that PKG II could be secreted out of the cell and existed in the supernatant of cultured cells and human and mouse serum.…”
Section: Cell Ell B Biology Iology I International Nternationalsupporting
confidence: 78%
“…As a serine/threonine protein kinase localized on the inner side of the cell membrane by myristoylation of the second glycine at the N‐terminal of the peptide chain, our lab found that PKG II inhibited the activation of several RTKs by phosphorylating specific sites in the intracellular domain of RTKs (Lan et al, 2019 ; Y. Wang et al, 2018 ; Wu et al, 2016 ). Based on the discovery of the secretion of PKG II, whether secretory PKG II inhibits the activation of RTKs by phosphorylating the extracellular segment of RTKs is worthy of further discussion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RPTKs are key players in the regulation of numerous fundamental cellular processes such as growth, adhesion, differentiation, and migration 26. In GC cells, the MAPK–ERK and PI3K– AKT signaling pathways affect RPTK activity 27. Therefore, we speculated that the effect of other regulatory factors in GC leads to PI3K–AKT signaling pathway feedback acting on STYK1, thereby reducing its expression.…”
Section: Discussionmentioning
confidence: 99%